Analyzing customer profitability in hotels using activity based costing - Ana Rita Faria; Leonor Ferreira; Duarte Trigueiros (Tourism & Management Studies)
This paper investigates the use of customer profitability analysis (CPA) in four and five star hotels located in Algarve (Portugal). Traditional accounting systems have been criticized for focusing on product, service or department profitability, and not on customer profitability, thus failing to provide effective information to marketing-related decisions. Results are reported by operating departments, whilst marketing activities focus on customer market segments. Recognizing the growing emphasis on customer value creation, and to overcome the mismatch between the provision and use of information in hotels, CPA techniques have been suggested. Notwithstanding their benefits, namely a strategic focus, hotels still apply traditional techniques. A structured questionnaire collected through personal interviews showed that CPA is far from widespread in hotel management; instead, hotels accumulate costs in profit centers and in cost centers. None of the surveyed hotels had adopted activity based costing, despite this technique being viewed as the most appropriate to calculate individual customer profitability.